Interactive narratives and transmedia storytelling creating immersive stories across new media platforms - McErlean, Kelly
a"Interactive Narratives and Transmedia Storytelling provides media students and industry professionals with strategies for creating innovative new media projects across a variety of platforms. Synthesizing ideas from a range of theorists and practitioners across visual, audio, and interactive media, Kelly McErlean offers a practical reference guide and toolkit to best practices, techniques, key historical and theoretical concepts, and terminology that media storytellers and creatives need to create compelling interactive and transmedia narratives. McErlean takes a broad lens, exploring traditional narrative, VR and AR, audience interpretation, sound design, montage, the business of transmedia storytelling, and much more. Written for both experienced media practitioners and those looking for a reference to help bolster their creative toolkit or learn how to better craft multi-platform stories, Interactive Narratives and Transmedia Storytelling serves as a guide to navigating this evolving world. An accompanying eResource includes links to other interactive narrative and transmedia resources and videos"--Provided by publisher.